The problem of values in humanistic and existential psychology - LEPEŠKIENĖ, VITALIJA (Psichologija, 1997)
ln the article perspectives of the representatives of humanistic (C. Rogers, A. Maslow) and existential psychology (V. Frankl, R. May) towards the issue of values are discussed. Though the authors assert that values and individuals’ relations to them are essential in human life, none of them gives an articulated definition of the concept. Representatives of humanistic and existential psychology strongly disagree about the locus of the values: A. Maslow maintains that values are of an intrinsic, biological nature while V. Frankl and R. May assert that values are not given to us by nature and are, rather, raised to us as tasks to be fulfilled. All the authors agree that failure to fulfill one’s values leads to serious psychological disorders that are not pathological but rather a part of the human condition. A therapist’s relation to his/her own values is claimed to be the crucial factor affecting his/her professional life as well as the process and content of therapy.